Wissensnetze im Stadtumbau des Landes Brandenburg — Analysen und Empfehlungen - Büttner, Kerstin; Droste, Christiane; Lange, Bastian; Mahnken, Gerhard (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
With all their strength, the East German states are struggling to maintain the highly mobile resource “human capital”. In the meantime, there was even a suggestion to reimburse the tuition fees to everybody who would also after his degree stay in the state where he or she studied. Increasingly the question arises, how knowledge building infrastructures might, beyond their function as resource for learning and training, promote the development of attractive socio-spatial areas. The following article will analyse four knowledge networks and their key actors, practitioners and policies and will provide recommendations for action, which are probably relevant even out of range of the state of Brandenburg.